Fasakh as an Instrument of Protection and Justice in Marriage: An Analysis of Zainuddin al-Malibari’s Thought in Fathul Mu’in and Its Relevance in Indonesia - Rasyidin Rasyidin; Abdul Manaf (Jurnal El-Thawalib, 2026)
This study is motivated by the importance of mechanisms for the dissolution of marriage that do not merely emphasize formal-legal aspects, but also ensure the protection of rights and justice for the parties involved. In Islamic law, fasakh serves as one such instrument; however, in practice, it is often narrowly understood and not optimally implemented in society. Furthermore, social dynamics and the increasing number of injustices within households demand a more comprehensive understanding of the concept of fasakh as a just solution. Therefore, this study aims to analyze the thought of Zainuddin al-Malibari in Fathul Mu‘in regarding the concept of fasakh and to examine its relevance within the Indonesian marriage law system. This research employs a qualitative method with a library research approach. The approaches used are normative and historical. The primary source is the classical text Fathul Mu‘in, while the secondary data include classical and contemporary fiqh books, scholarly journal articles, and Indonesian legal regulations, particularly the Compilation of Islamic Law. Data collection is conducted through documentation studies, and data analysis uses a descriptive-analytical method with deductive and comparative reasoning patterns. The findings of this study indicate that fasakh, in the thought of Zainuddin al-Malibari, functions as an instrument of protection for parties harmed within a marriage, such as in cases of physical or psychological defects, inability to provide maintenance, neglect, and other forms of harm. This concept underscores the importance of substantive justice and the protection of individual rights within marital relationships. In the Indonesian context, the principles of fasakh have strong relevance to positive law, particularly within the Compilation of Islamic Law, which also accommodates grounds for divorce in order to realize balanced protection and justice for both husband and wife.